A Personal Relationship with the Mysteries: (Re)discovering the Enchanted Garden Through Movement and the Body - Kieft, Eline (Théologiques, 2017)
This article investigates the possible role of improvised, conscious dance movement in nature as a way of reclaiming our direct experience of the metaphysical. I first discuss some aspects of the body and embodiment, not as contradictory with but absolutely essential to spirituality. I briefly touch on the possibility of embodied ecstasy, as well as various elements of embodiment such as awareness, alignment, presence, and connection. Then, after introducing some notions of dance and spirituality in various contexts, I zoom in on the ingredients of improvised movement as a way of negotiating the unknown, unpacking the possibilities of movement improvisation as a spiritual practice. Thirdly, I consider the potential for waking up to the sacred all around us, when movement practice is brought out into nature. Finally, I weave these threads together in some concluding thoughts on the role that dance can play in enhancing mystical participation in an enchanted world.